2014
DOI: 10.1186/1471-2393-14-285
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section in Shanghai: women’s or healthcare provider’s preferences?

Abstract: BackgroundCesarean section (CS) rate has increased rapidly over the past two decades in China mainly driven by non-medical factors. This study was to compare recalled preferences for CS among first-time mothers in early and late pregnancy with actual delivery mode; to explore factors related to CS preference and CS performed without medical indications; and to consider the role of healthcare providers in delivery mode preferences.MethodsAn anonymous questionnaire survey, combined with data on CS indications ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 24 publications
2
49
0
4
Order By: Relevance
“…Women's requests for caesarean section have been cited as a reason for the rising rates but only a minority of women in a wide range of countries have expressed a preference for caesarean section . Studies in a number of countries have shown that many women who ended up having caesarean section would have preferred vaginal delivery and are influenced by models of care and healthcare providers’ preferences . The results of the WHO global surveys of maternal and perinatal health in Latin America and Asia have pointed to the potential dangers and excessive costs associated with caesarean sections that are clinically unnecessary …”
Section: Discussionmentioning
confidence: 99%
“…Women's requests for caesarean section have been cited as a reason for the rising rates but only a minority of women in a wide range of countries have expressed a preference for caesarean section . Studies in a number of countries have shown that many women who ended up having caesarean section would have preferred vaginal delivery and are influenced by models of care and healthcare providers’ preferences . The results of the WHO global surveys of maternal and perinatal health in Latin America and Asia have pointed to the potential dangers and excessive costs associated with caesarean sections that are clinically unnecessary …”
Section: Discussionmentioning
confidence: 99%
“…The Caesarean section rates above 30% observed in Middle East/Europe and Latin America regions likely reflect unnecessary interventions, and there is evidence to suggest that these are being differentially provided to the rich and higher in the private sector. A substantial literature elucidates how private providers are incentivised to overperform Caesarean sections either because they are financially more lucrative, because they can be conveniently scheduled or because of women's demands for care from one individual [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK the CS rate increased from 12 to 29% between 1990 and 2008 (Betran et al, 2007). In the USA in 2011 one in three women delivered by CS, whereas in China the CS rates have even risen from 2% in 1985 to 36-58% in 2010 and in Brazil from 15% in 1970 to even 80% in the private sector in 2004 (Barros et al, 2011;Deng et al, 2014;Feng et al, 2014;Osterman and Martin, 2014). There is no discussion that a CS is a lifesaving procedure for some women, for example for women with placenta praevia or truly obstructed labour, or for babies with proven distress either antenatal or intrapartum.…”
Section: Introductionmentioning
confidence: 99%